Nine-year exposure to residential greenness and the risk of metabolic syndrome among Luxembourgish adults: A longitudinal analysis of the ORISCAV-Lux cohort study. (May 2023) - Tharrey, Marion; Klein, Olivier; Bohn, Torsten; Malisoux, Laurent; Perchoux, Camille
Abstract: Growing evidence shows a beneficial effect of exposure to greenspace on cardiometabolic health, although limited by the cross-sectional design of most studies. This study examined the long-term associations of residential greenness exposure with metabolic syndrome (MetS) and MetS components within the ORISCAV-LUX study (Wave 1: 2007–2009, Wave 2: 2016–2017, n = 395 adults). Objective exposure to residential greenness was measured in both waves by the Soil-Adjusted Vegetation Index (SAVI) and by Tree Cover Density (TCD). Linear mixed models were fitted to estimate the effect of baseline levels and change in residential greenness on MetS (continuous score: siMS score) and its components (waist circumference, triglycerides, HDL-cholesterol, fasting plasma glucose and systolic blood pressure), respectively. This study provides evidence that an increase in SAVI, but not TCD, may play a role in preventing MetS, as well as improving HDL-cholesterol and fasting plasma glucose levels. Greater baseline SAVI was also associated with lower fasting plasma glucose levels in women and participants living in municipalities with intermediate housing price, and greater baseline TCD was associated with larger waist circumference. Overall, findings suggest a mixed impact of increased greenness on cardiometabolic outcomes. Further longitudinal research is needed to better understand the potential effects of different types of greenness exposure on cardiometabolic outcomes. Highlights: Residential greenness may have a beneficial effect on cardiometabolic health. A mixed impact of 9-year increase in greenness on cardiometabolic outcomes was observed. Increase in green vegetation cover was associated with lower metabolic syndrome. Increase in green vegetation cover also improved HDL-c and fasting plasma glucose. Increase in tree cover density did not improve cardiometabolic health.